Alteration of the Enantioselective Toxicity of Diclofop Acid by Nonylphenol: Effect on Ascorbate‐Glutathione Cycle in Microcystis Aeruginosa. Issue 6 (22nd April 2016) - Zhang, Qiong; Song, Qin; Li, Jialiang; Zou, Meiling; Zhang, Chenxi; Zhang, Quan
Abstract: Theenantioselective effects of chiral compounds have been the subject of extensive studies in recent years due to their important implications for contaminant behavior and risk as well as the design of drug and pesticide formulations. The potential alterations ofenantioselectivity, however, still remain elusive from the available data suggesting the effects of numerous environmental factors and the coexisting achiral and chiral compounds. Herein we studied the effect of nonylphenol (NP), a ubiquitous contaminant and ingredient in pesticide formulation, on theenantioselectivity of diclofop acid (DC) through ascorbate‐glutathione (AsA‐GSH) cycle in Microcystis aeruginosa . Theenantioselectivity of DC in the AsA and GSH antioxidant defense system of M . aeruginosa was affected significantly by the addition of NP. Specifically, although R‐ DC and S‐DC were added with an equal toxic concentration (at their EC50 values), NP addition to the DC treatments altered the enantiomeric ratios of the activities of monodehydroascorbate reductase (MDHAR) and glutathione reductase (GR), key enzymes in the regeneration of AsA and GSH, respectively. NP also modified the enantiomeric ratios of AsA and GSH levels in both the AsA and GSH antioxidant defense systems of M . aeruginosa . Overall, the oxidative damage induced by R‐DC was further deteriorated, whereas that induced by S‐DC was alleviated after NP addition. These alteredenantioselectivities indicate a need to reexamine the risks and biological effects of chiral compounds in the complex environmental matrices containing a multitude of other chemicals, including commercial chiralagricultural chemicals . Chirality 28:475–481, 2016 . © 2016 Wiley Periodicals, Inc. Abstract :